2017
DOI: 10.1161/atvbaha.116.308834
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Cholesterol Elicits Arterial Wall Inflammation and a Multilevel Cellular Immune Response in Humans

Abstract: Patients with FD have increased arterial wall and cellular inflammation. These findings imply an important inflammatory component to the atherogenicity of remnant cholesterol, contributing to the increased cardiovascular disease risk in patients with FD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
81
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 22 publications
5
81
1
1
Order By: Relevance
“…Importantly, foamy monocytes infiltrate into arterial walls and contribute to the development of atherosclerosis in mice with hypercholesterolaemia 6 . The observations made by Bernelot Moens et al of circulating monocytes with intracellular lipid accumulation (‘foamy monocytes’), increased monocyte expression of chemokine receptors and adhesion molecules, and enhanced monocyte migration in patients with FH 2 or FD 5 also support an important role of these foamy monocytes in the development of ASCVD in humans with hyperlipidaemia — severe hyperlipidaemia in particular. Furthermore, the findings of this study suggest that monocyte lipid accumulation in patients with FH did not rely on the LDL receptor and could be reversed by PCSK9-inhibitor treatment 2 .…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…Importantly, foamy monocytes infiltrate into arterial walls and contribute to the development of atherosclerosis in mice with hypercholesterolaemia 6 . The observations made by Bernelot Moens et al of circulating monocytes with intracellular lipid accumulation (‘foamy monocytes’), increased monocyte expression of chemokine receptors and adhesion molecules, and enhanced monocyte migration in patients with FH 2 or FD 5 also support an important role of these foamy monocytes in the development of ASCVD in humans with hyperlipidaemia — severe hyperlipidaemia in particular. Furthermore, the findings of this study suggest that monocyte lipid accumulation in patients with FH did not rely on the LDL receptor and could be reversed by PCSK9-inhibitor treatment 2 .…”
mentioning
confidence: 90%
“…Most previous studies indicated that levels of intermediate and/or nonclassical monocytes were increased in hyperlipidaemia and associated with ASCVD. Bernelot Moens et al reported that the above phenotypic changes occurred mainly in classical monocytes, and that the ratios of each monocyte subset did not change in patients with FH or FD compared with healthy controls 2,5 . By contrast, Christensen et al showed that, compared with healthy controls, children with FH, particularly those with low HDL-cholesterol levels, had higher circulating intermediate and nonclassical monocytes and lower levels of classical monocytes 10 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported the presence of lipid-laden monocytes in a setting of postprandial hyperlipidemia (6), genetically elevated levels of remnant cholesterol (28), and familial hypercholesterolemia (FH) (29). To assess the applicability of the NRQ in disease settings, we included pilot analyses of: a) three heterozygous FH patients (30) currently not receiving therapy due to statin-associated muscle symptoms (31) and compared them to age and gender matched healthy controls and b) three obese subjects who underwent an oral fat load.…”
Section: Clinical Validationmentioning
confidence: 99%